PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL TERHADAP KINERJA GURU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA SMK NEGERI DI ACEH UTARA - Mahdi Mahdi; Aiyub Aiyub; Darmawati Darmawati (Universitas Malikussaleh, 2021)
ABSTRAKThe teacher is one of the most important components in improving the intelligence of the nation's children. Teacher performance is an important factor in realizing these goals. Efforts to improve teacher performance are one of the priorities of the country. This study aims to determine the effect of transactional and transformational leadership styles on teacher performance through job satisfaction. The data used are primary data by distributing questionnaires to 144 teachers at the State Vocational High School (SMK) in North Aceh Regency. The method used to analyze data is the Structural Equation Modeling (SEM) Method with the Amos device. The results found that transactional leadership and transformational leadership have a significant effect on job satisfaction and teacher performance and job satisfaction has a direct effect on teacher performance. Furthermore, it was found that job satisfaction mediated the effect of transactional leadership and transformational leadership on the performance of North Aceh District Vocational School teachers. Based on the results of the study, it is expected that school leaders or principals, to improve teacher performance, need to maintain the application of transactional and transformational leadership styles and give priority to increasing job satisfaction.